2021
DOI: 10.3390/ijerph18157889
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Practice and Association between Characteristics and Experiences of Mothers Living in Bangkok

Abstract: Although the benefits of breastfeeding are widely recognized, only 14% of mothers in Thailand exclusively breastfed their children during the first six months of their lives in 2019, which dropped from 23% in 2016. This study aimed to assess the prevalence of exclusive breastfeeding (EBF) up to six months, current breastfeeding patterns, and key determinants that influence six-month EBF among mothers residing in Bangkok, Thailand. A cross-sectional study was conducted using a self-administered questionnaire su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…[36][37][38][39] Therefore, empowering mothers to develop breastfeeding intentions and self-efficacy and equip them with necessary technical skills such as latching and the positioning of the baby are critical for successful EBF. 7,24,40 This study confirms the critical role of health professionals in providing support at all stages, from pregnancy to delivery and post-partum and beyond. Healthcare professionals should aim to strengthen mothers' intrinsic motivation towards EBF from early pregnancy onwards, while intrinsic motivation includes desire for self-control, concerns about baby's health and concerns about mother's health.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[36][37][38][39] Therefore, empowering mothers to develop breastfeeding intentions and self-efficacy and equip them with necessary technical skills such as latching and the positioning of the baby are critical for successful EBF. 7,24,40 This study confirms the critical role of health professionals in providing support at all stages, from pregnancy to delivery and post-partum and beyond. Healthcare professionals should aim to strengthen mothers' intrinsic motivation towards EBF from early pregnancy onwards, while intrinsic motivation includes desire for self-control, concerns about baby's health and concerns about mother's health.…”
Section: Discussionsupporting
confidence: 73%
“…Evidence shows that poor-latching and insufficient breastmilk supplies are common reasons for EBF discontinuation. 23,25,40,42 Despite health professionals' critical roles, existing breastfeeding support for Thai mothers, particularly during the early post-partum period, is still inadequate and needs significant reform; 43,44 only 7.7% of infants in Thailand were put to the mother's breast after birth and only 34% were initially breastfed within an hour after birth in 2019. 6 Inadequate breastfeeding follow-up is a result of a shortage of lactation counselors and other competing responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers in the current study possess characteristics that can act as facilitators and also as barriers to breastfeedexclusively for six months.Research shows that younger and less educated mothers without prior breastfeeding experience are likely to experience barriers to breastfeed exclusively 24 . Returning to work and returning to school for a breastfeeding mothers are barriers to continuation of exclusive breastfeeding and these two factors can also lead to early weaning 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) and United Nations International Children's Emergency Fund (UNICEF) recommend exclusive breastfeeding until 6 months old, with continued breastfeeding to 2 years old or beyond (1). Nevertheless, breastfeeding duration in China is still far below the global nutrition targets (2). Several studies have reported that maternal antenatal intention to breastfeed is a strong predictor of actual duration of breastfeeding (3).…”
Section: What Are the Implications For Public Health Practice?mentioning
confidence: 99%
“…Nevertheless, breastfeeding duration in China is still far below the global nutrition targets ( 2 ). Several studies have reported that maternal antenatal intention to breastfeed is a strong predictor of actual duration of breastfeeding ( 3 ). Maternal postpartum intention could be much more associated with actual breastfeeding duration because of shorter time intervals and fewer impeding factors present during pregnancy, compared to maternal antenatal intention.…”
mentioning
confidence: 99%